The Influence of National Culture on Educational Videos: The Case of MOOCs - Bayeck, Rebecca Yvonne; Choi, Jinhee (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
This paper discusses the influence of cultural dimensions on Massive Open Online Course (MOOC) introductory videos. The study examined the introductory videos produced by three universities on Coursera platforms using communication theory and Hofstede’s cultural dimensions. The results show that introductory videos in MOOCs are influenced by the national culture of the country in which the university is based. Based on this finding, this paper raises interesting questions about the effect of these cultural elements on potential learners from different countries and cultures around the world. The paper also makes suggestions about introductory video production in MOOCs.